Finite element modeling of nano porous sintered silver material - Meyghani, B. (Springer Science and Business Media Deutschland GmbH, 2020)
In the packaging industry, the conventional lead-based solders have gradually become obsolete because of Hazardous Substances regulations and the rapid advancement of alternatives in microelectronics production. Sintered silver paste is proposed to bond the chips and substrates, because compared with other metals used in the electronic industry, silver has better thermal and electrical conductivity, a higher melting point, and it has less susceptible to oxidation. However, after sintering, a considerable pore fraction will be existing in the material, and compared with bulk silver, after the sintering process the material density decreases. Therefore, the effect of the pore distribution on elastic and thermal properties of the sintered silver pastes during aging is one of the main parameters for modeling the whole electronic system under operating conditions. So far, there are limited studies for investigating the effect of the material aging on the microstructural level. Hence, this study focuses on examining the effect of the morphology and pore distribution in the material responses as well as determining the quantitative nanostructure relationship between the material properties of the as-sintered and aged. In this study, a home-built MATLAB® code was developed in order to increase the quality of images. Mimics® software was used to convert the images to solid 3D representative volume elements. Numerical homogenization technique was also used to evaluate as-sintered and aged microstructure properties. The results show that there is a temporary pattern relationship between the stress and the time of the heat treatment. To validate the developed model, both as-sintered and aged materials have gone through several published work to determine changes of the material properties. © Springer Nature Singapore Pte Ltd 2020.